INTRASPECIFIC VARIATION OF COMMON CARP (Cyprinus carpio Linnaeus (1758): A KARYOTYPE ANALYSIS - YAQOOB, SHABEENA; SRIVASTAVA, PRADEEP (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
There is no information on karyotyping of Cyprinus carpio in the country. The objective of this study is to detect and differentiate between the karyotypical structure of Cyprinus carpio from the two intra-specific river systems of one tropical Narmada River, Madhya Pradesh, and the temperate Jhelum River, Kashmir. Karyotypes of Species' were classified based on size, type, and structure, such as metacentric (M), submetacentric (SM), subtelocentric (ST), and acrocentric/telocentric (A/T). Methods of chromosome preparations were in detail described by RAB (1981). Their findings revealed that interspecific and even intergeneric differences of Cyprinus carpio of two rivers differences are if any, negligible. All these facts show that the karyotype conservatism occurs in the Cyprinidae subfamily. This conclusion is consistent with the same evolutionary methods of karyotype.